Histopathological Studies Of Spontaneous Kidney Lesions In Goats (Capra Hircus) - Bamnele, Rakesh; Garg, U.K.; Shukla, S.; Shukla, P.C.; Das, G.; Singh, S.; Shakya , P. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present investigation was carried out to study the spontaneous occurrence of various pathomorphological and histopathological alterations in the kidneys of goats. Examination of kidneys from a total number of 500 goats ranging from 1 to 6 years of age were conducted . Out of 500 animals, 46 (9.2%) cases were found to be affected with various pathological conditions. The fatty degeneration was one of the pathological conditions encountered highest in kidney, i.e. 1.6% followed by vascular abnormalities (1.4%), interstitial nephritis (1.2%), glomerulonephritis (1.0%), amyloidosis (0.8%), nephrolithiasis and calcification (0.6%), hypertrophy and hypoplasia, renal infarction, embolic nephritis, and pigmentation each (0.4%),and hydronephrosis and pyelonephritis (0.2%).